The distinctiveness of East Germany in the light of the concept of longue durée - Kowalski, Mariusz (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The reunification of Germany in 1990 revealed a clear difference between the two parts of the country. This is visible, for example, in the political sympathies revealed during the elections. These differences are most often explained by the 45-year period of the country’s division and the functioning of two different political and socio-economic systems. Nevertheless, the differences between the East and West of Germany were noticed even before 1945. The East later became part of Germany and was initially inhabited by Slavic peoples. The local German society was created by mixing the settlers from the west with the local Slavic people. The relics of this process are linguistic differences (toponymy, anthroponymy, borrowings in local dialects) that persist to this day, as well as different features revealed in genetic research. As a result of the interaction between local conditions and ideas flowing from the West, a completely new settlement, economic and legal system was also created. It can be assumed that the emergence of these conditions also influenced the later development of the socio- -economic and political system in this area. Large unified principalities (Brandenburg, Saxony, Pomerania, Mecklenburg, Prussia) were established in the east, so there was no room for political and systemic pluralism as in the west (free cities, free nobility of the Reich). The local princes gained a dominant position, basing their power on subordinated vassal nobility. There was a weakness of the cities and the bourgeoisie. In these conditions, in the process of the so-called secondary feudalization, formed the separateness of the so-called Ostelbien, associated with the dominant role of the nobility and the manorial serf economy. The liquidation of the feudal system also took a specific form here due to the so-called the Prussian road to capitalism in agriculture. It maintained the privileged position of the nobility (Junkers) in the socio-economic and political life of East Germany. Initially, autocracy was associated with conservative tendencies. Later, above-average sympathies for left-wing movements developed here. The conservatism of the nobility and the rich peasantry coexisted with the leftism of a large number of hired workers in agriculture. The influence of the authoritarian socialist system overlapped with these earlier conditions, partially in harmony with them, further strengthening the separateness of East Germany from the West.